PERANCANGAN CENDERAMATA SEBAGAI BRANDING DESA WISATA, KAMPUNG SATWA KEDUNG BANTENG, MOYUDAN, YOGYAKARTA - Koniherawati; Nugroho, Gregorius Delon Ajidamara; Nathanael, Michelle Aurelia; Madyaningrana, Kukuh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2024)
Duta Wacana Christian University in Yogyakarta has established a partnership with the Animal Village in Kedung Banteng Village, Moyudan District, Sleman Regency, D.I.Y. This collaboration involves the Product Design lecturers, Biotech, and two Product Design students from DWCU, resulting in training for creating souvenirs. The presence of the Animal Village at RT 06 / RW 16 Kedung Banteng is unique and captivating. It began with a resident's hobby of caring for animals, which evolved into an educational eco-tourism village for local schools and communities from various regions. The existence of its place offers the opportunity to learn about various protected animal species, their habitats, and plants cultivated to support their survival. This inspired the academic team to assist in developing the educational eco-tourism village through promotional strategies using memorable souvenirs that can serve as an identity (branding) to be cherished and recognized more widely. The activities include skills training and knowledge about pottery and batik, which are part of Java's rich cultural heritage, utilizing the natural resources available in the area. The well-planned souvenir concept will serve as innovative visual branding and an effective promotional media. This service is conducted through technical training, involving direct observational data collection, interviews, and participatory methods to create products that serve as promotional media and examples for other villages to love and protect nature.